Homophily in the Guise of Cross-Linking: Political Blogs and Content. (September 2014) - Nahon, Karine; Hemsley, Jeff
This study examines the behavior of influential political blogs (conservative and liberal) in reference to external viral content during March 2007 and June 2009. We analyze homophily and cross-ideological (heterophily) practices. We propose a multidimensional model that employs both qualitative and quantitative methods for examining homophily behaviors by looking at three dimensions: blog-to-blog, blog-to-video, blog post-to-video. Findings show that while homophily patterns prevail, some limited occurrences of cross-ideological practices exist. The cross-linking practices may include deliberative motives, but in essence they are not created for the purposes of discourse. Instead, these cross-linking practices strengthen previously held political stances of the users who create them and negatively portray and reframe content of alternative views. This represents homophily in the guise of cross-linking.